EFFECTIVENESS LEARNING LAPTOPS AND HANDPHONE TO UNDERSTANDING STUDENT LEARNING - Rahmansyah Fadlul Al Karim Rambe; Masdalena Masdalena; Kintan Aulia Coal; Lutfiah Rahmah (Pena Cendekia Insani, 2024)
smartphone use in supporting learning activities in circles student. With use analysis. Results study show effectiveness use smartphones in circles student support activity Study student in matter increase outlook student And Also make it easy student in Study, do task nor looking for material lesson.